2020
DOI: 10.1590/1807-1929/agriambi.v24n10p656-663
|View full text |Cite
|
Sign up to set email alerts
|

Morphophysiological responses and mechanisms of salt tolerance in four ornamental perennial species under tropical climate

Abstract: Salinity affects growth and quality of ornamental plants, but studies on mechanisms of salt tolerance in these plants are scarce, particularly under tropical climate conditions. Thus, the morphophysiological leaf responses of four tropical ornamental species were studied, in order to identify the mechanisms involved in the tolerance to salinity and their potentials to be irrigated with brackish water. The research was conducted in a greenhouse using a completely randomized block design, in a 10 x 4 factorial s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 29 publications
(38 reference statements)
2
23
1
Order By: Relevance
“…Under salinity conditions, the instantaneous carboxylation efficiency is influenced by the increase in internal CO2 concentration, due to the decrease in photosynthetic rate (Dias et al, 2018). Opposite results to the present study were found by Lacerda et al (2020) when analyzing the morphophysiological responses and salt tolerance mechanisms in four perennial ornamental species grown in a greenhouse, found a decrease in A/Ci with increasing electrical conductivity of irrigation water.…”
Section: Resultscontrasting
confidence: 75%
See 1 more Smart Citation
“…Under salinity conditions, the instantaneous carboxylation efficiency is influenced by the increase in internal CO2 concentration, due to the decrease in photosynthetic rate (Dias et al, 2018). Opposite results to the present study were found by Lacerda et al (2020) when analyzing the morphophysiological responses and salt tolerance mechanisms in four perennial ornamental species grown in a greenhouse, found a decrease in A/Ci with increasing electrical conductivity of irrigation water.…”
Section: Resultscontrasting
confidence: 75%
“…The use of irrigated agriculture becomes fundamental for a safe production (Léllis et al, 2022;Lacerda et al, 2020). This practice becomes indispensable in regions that present a high climatic variability, as is the case of the semi-arid region of Brazil; however, the vast majority of water sources available for irrigation in this region present a high content of salts (Fernandes et al, 2016;Pereira et al, 2019;Dias et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For E (transpiration), a reduction was observed in both cultivars in all treatments under water deficit ( Figure 1 c). The reduction in E comes from stomatal closure since plants under water restriction or at high temperatures tend to close their stomata so as not to lose water, as highlighted in studies with sesame plants under water deficit [ 28 , 29 ]. E is a crucial factor for processes such as leaf temperature regulation.…”
Section: Resultsmentioning
confidence: 99%
“…In the semi-arid region of north-eastern Brazil, some of the water sources used in irrigation are considered brackish, a determining factor for soil salinization and a reduction in crop yield. An excess of salts in the irrigation water promotes stress in the plants and has a negative effect on chlorophyll biosynthesis, photochemical effi ciency and gas exchange, and consequently on production, due to the action of specifi c ions such as sodium (Na + ) and chlorine (Cl -) (NUNES et al, 2017).…”
Section: Introductionmentioning
confidence: 99%